IMPLEMENTASI PERDA KABUPATEN KLATEN TENTANG RETRIBUSI JASA UMUM (PASAR) PERSPEKTIF HUKUM ISLAM - Windarti, Windarti; Wicaksono, Andi (Fakultas Syariah, Universitas Islam Negeri Raden Mas Said Surakarta, 2021)
Abstract Retribution is a collection of money by the government (municipalities and so on) in return for services. The collection of market retribution in each region is regulated by the government to run effectively. Such is the case with the collection of market levies at the Cork Market which is regulated in the Klaten Regency Regional Regulation Number 18 of 2011 concerning Public Service Retribution. Judging from the development of the Gabus Market in the Klaten area, it looks like it is still in a bad condition. So the problem is how to implement the Regional Regulation related to market retribution and how to implement the Regional Regulation from the perspective of Islamic Law. The purpose of this study was to determine the implementation of these regional regulations related to the implementation of market service fees in the Gabus Market and the view of Islamic law on the implementation of market fees in the Gabus Market. The research method uses a field qualitative research type. Sources of data used are primary and secondary. The result of this research is that the implementation of Regional Regulation No. 18 of 2011 concerning Public Service Fees (Markets) in the Gabus Market has not been implemented properly, namely in the provision of services and the provision of facilities. In the procedure for implementing the collection of levies, the officer does not give a ticket as proof of payment, the lack of awareness of traders who still do not want to pay and the lack of firmness of officers who do not give sanctions. The market retribution income at Pasar Gabus is quite good. Meanwhile, in implementation according to Islamic law, there is still a gap between the rights and obligations of traders. Keywords: Islamic Law; Implementation; Market Retribution. Abstrak Retribusi adalah pungutan uang oleh pemerintah (kota praja dan sebagainya) sebagai balas jasa. Pemungutan retribusi pasar di setiap daerah diatur oleh pemerintah agar berjalan dengan efektif. Seperti halnya pemungutan retribusi pasar di Pasar Gabus yang diatur dalam Peraturan Daerah Kabupaten Klaten Nomor 18 Tahun 2011 Tentang Retribusi Jasa Umum. Dilihat dari perkembangan Pasar Gabus di wilayah Klaten terlihat masih dalam keadaan yang kurang baik. Sehingga permasalahannya bagaimana implementasi Peraturan Daerah tersebut terkait retribusi pasar dan bagaimana implementasi Peraturan Daerah tersebut dari perspektif Hukum Islam. Tujuan penelitian ini adalah untuk mengetahui implementasi Peraturan Daerah tersebur terkait dalam pelaksanaan retribusi pelayanan pasar di Pasar Gabus dan pandangan hukum Islam terhadap pelaksanaan retribusi pasar di Pasar Gabus. Metode penelitian menggunakan jenis penelitian kualitatif lapangan. Sumber data yang digunakan adalah primer dan sekunder. Hasil dari penelitian ini adalah Implementasi Peraturan Daerah Nomor 18 Tahun 2011 Tentang Retribusi Jasa Umum (Pasar) di Pasar Gabus belum di implementasikan dengan baik, yaitu pada pemberian pelayanan dan penyediaan fasilitas. Pada prosedur pelaksanaan pemungutan retribusi tidak diberikan karcis oleh petugas sebagai bukti pembayaran, kurangnya kesadaran dari pedagang yang masih belum mau membayar dan kurangnya ketegasan petugas yang tidak memberikan sanksi. Pendapatan retribusi pasar di Pasar Gabus sudah cukup baik. Sedangkan dalam pelaksanaan menurut hukum Islam, masih ada kesenjangan antara hak dan kewajiban dari pedagang. Kata Kunci : Hukum Islam; Implementasi; Retribusi Pasar.